MODEL STRATEGIS MANAJEMEN SARANA DAN PRASARANA BERBASIS DASAR-DASAR MPI DALAM PENGUATAN KELEMBAGAAN PAUD DI RA HIDAYATUTTAUHID NAGREG - Siti Nuraisyah Warohmah; Mulyawan Safwandy Nugraha (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The management of educational facilities and infrastructure is a crucial determinant of service quality and institutional strengthening in Early Childhood Education (ECE). A common challenge faced by many ECE institutions, including RA Hidayatut Tauhid Nagreg, is the absence of strategic, systematic, and value-based facility management, which limits the optimal utilization of existing resources in supporting sustainable learning and institutional development. This study aims to analyze and formulate a strategic model of facilities and infrastructure management grounded in the principles of Islamic Education Management (IEM) to strengthen the institutional capacity of ECE at RA Hidayatut Tauhid Nagreg. The research employed a qualitative approach with a case study design, utilizing in-depth interviews, participatory observation, and document analysis as data collection techniques. Data were analyzed using an interactive qualitative model involving data reduction, data display, and conclusion drawing. The findings reveal that although RA Hidayatut Tauhid Nagreg possesses relatively adequate facilities and infrastructure to support early childhood learning, their management remains predominantly operational rather than strategic, particularly in planning, inventory systems, maintenance, and stakeholder involvement. The study concludes that institutional strengthening in ECE can be achieved through optimizing facilities and infrastructure management integrated with IEM principles, enabling educational facilities to function not only as technical resources but also as strategic instruments for institutional sustainability and improved quality of early childhood education services.